(untitled) (American Journal of Business Management, Economics and Banking, 2023)
This study examined the relationship between structural capital investment and the financial performance of quoted manufacturing firms in Nigeria, with specific attention to Return on Assets of manufacturing firms. Utilizing an ex-post facto research design, this study employed secondary data extracted from the annual reports of 30 publicly quoted manufacturing companies in Nigeria. A total of 300 observations were analyzed using panel data regression models. The results revealed a statistically significant positive relationship between structural capital investment and ROA, suggesting that investment in organizational structure, systems, and processes could contribute to efficient asset utilization. Conversely, a non-significant relationship was observed between structural capital investment and EPS, raising questions about the immediate impact of such investments on shareholder value in the Nigerian manufacturing sector. The study recommends that manufacturing companies should strategically invest in structural capital such as organizational culture, information systems, and processes, with a focus on long-term asset optimization, given its positive relationship with ROA.